Material Development in Production Ecrite Intermediaire by Sipda to Improve the Writing Ability the Student of French Departement at Faculty of Languages and Arts at One of State Universities in Northen Island of Indonesia - Tengku Ratna Soraya; Zulherman; Nurilam Harianja; Hesti Fibriasari (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
This study aims to develop teaching materials in Production Ecrite Intermediare course to improve the writing ability the student of french departement at Faculty of Languages and Arts at One of State Universities in Northen Island of Indonesia by using SIPDA. This research was conducted to response the condition of covid pandemic situation that uses distance learning courses where students learn from their own homes. This research followed the R & D model proposed by Borg & Gall with the procedure analysing the student’s need, collecting the ressource of development, design the material, evaluatingexisting the materials based on the validation of experts judgement, field testing, revising, and finishing the final product. This research was carried out in the French Language Education Study Program FBS UNIMED by developing SIPDA-based teaching materials in lectures, to find out that these teaching materials can improve the writing skills of students of French Language Education Study Program at FBS Unimed. The results of this study show that SIPDA is very effective in helping students to improve the writing ability of French texts. This research recommends to the lecturers of French courses in general to using SIPDA in the teaching and learning process of writing in the classroom of Production Ecrite Intermediaire.